Western and Central Asia. Satellite Imagery for the Study of Conservation and Restoration of Earthen Architecture. Research Carried Out between July and September 2022 - Volpi, Luca (e-Forschungsberichte des DAI, 2023)
Conservation and restoration of archaeological earthen architecture in the countries of Western and Central Asia is critical but challenging due to the tendency of earthen architecture to deteriorate once exposed to weathering and other decay agents. The paper presents a comparative analysis of the practices carried out in the area, with the use of satellite environmental and climatic data about rainfall, snow-ice cover, and average land surface temperature data for day and night. The aim is to propose an approach that gives the opportunity to compare the different practices employed and their effectiveness on the basis of various climatic and environmental elements.